2001
DOI: 10.1021/ja011253a
|View full text |Cite
|
Sign up to set email alerts
|

Acid-Catalyzed Isomerization of Pivalaldehyde to Methyl Isopropyl Ketone via a Reactive Protosolvated Carboxonium Ion Intermediate

Abstract: Quantitative rearrangement of pivalaldehyde to methyl isopropyl ketone is observed in acids such as trifluoromethanesulfonic acid, anhydrous HF, and trifluoroethyl alcohol-BF3 but not in trifluoroacetic acid. Studies in a mixture of trifluoroacetic acid and trifluoromethanesulfonic acid show that acids with H(o) < or = -11 are able to carry out complete isomerization. These results and density functional theory calculations at the B3LYP/6-31G level suggest that protonated pivalaldehyde undergoes further protos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
32
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 22 publications
2
32
0
Order By: Relevance
“…As we have shown earlier [4,5], the rearrangement of pivalaldehyde to methyl isopropyl ketone is strictly dependent on the acidity of the medium. Since pivalaldehyde and pivaloyl cation differ only by a hydride ion, it was worthwhile studying by theoretical methods the nature and reactivity of the pivaloyl ion under superacidic conditions as well as in the presence of hydride donors.…”
supporting
confidence: 54%
See 4 more Smart Citations
“…As we have shown earlier [4,5], the rearrangement of pivalaldehyde to methyl isopropyl ketone is strictly dependent on the acidity of the medium. Since pivalaldehyde and pivaloyl cation differ only by a hydride ion, it was worthwhile studying by theoretical methods the nature and reactivity of the pivaloyl ion under superacidic conditions as well as in the presence of hydride donors.…”
supporting
confidence: 54%
“…We suggested that the reaction proceeds through the intermediacy of gitionic diprotonated pivalaldehyde, which undergoes subsequent rearrangement to methyl isopropyl ketone. We explained the effect of acidity on pivalaldehyde rearrangement to methyl isopropyl ketone by monitoring the rearrangement under varying acidities provided by mixtures of trifluoroacetic acid and trifluoromethanesulfonic acid [4].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations